Application of Hydrogels in Heart Valve Tissue Engineering - Zhang, Xing (J Long Term Eff Med Implants, 2015)
With an increasing number of patients requiring valve replacement, there is heightened interest in advancing heart valve tissue engineering (HVTE) to provide solutions to the many limitations of current surgical treatments. A variety of materials have been developed as scaffolds for HVTE including natural polymers, synthetic polymers, and decellularized valvular matrices. Among them, biocompatible hydrogels are generating growing interest. Natural hydrogels, such as collagen and fibrin, generally show good bioactivity, but poor mechanical durability. Synthetic hydrogels, on the other hand, have tunable mechanical properties; however, appropriate cell-matrix interactions are difficult to obtain. Moreover, hydrogels can be used as cell carriers when the cellular component is seeded into the polymer meshes or decellularized valve scaffolds. In this review, we discuss current research strategies for HVTE with an emphasis on hydrogel applications. The physicochemical properties and fabrication methods of these hydrogels, as well as their mechanical properties and bioactivities are described. Performance of some hydrogels including in vitro evaluation using bioreactors and in vivo tests in different animal models are also discussed. For future HVTE, it will be compelling to examine how hydrogels can be constructed from composite materials to replicate mechanical properties and mimic biological functions of the native heart valve.